Localized Corrosion Behavior of Non-Equiatomic NiFeCrMnCo Multi-Principal Element Alloys. (10th September 2020) - Sahu, Sarita; Swanson, Orion J.; Li, Tianshu; Gerard, Angela Y.; Scully, John R.; Frankel, Gerald S.
Abstract: A series of single phase Ni38 Fe20 Crx Mn21–0.5x Co21–0.5x multi-principal element alloys (MPEAs) were fabricated and their localized corrosion behavior was tested in 0.6 M NaCl solution. These MPEAs were found to be susceptible to localized corrosion, exhibiting pitting at room temperature, as indicated by positive hysteresis loops and low repassivation potentials observed in cyclic potentiodynamic polarization experiments. The pitting resistance increased with increasing Cr content. Interestingly, even the MPEAs with low chromium content, Ni38 Fe20 Cr6 Mn18 Co18 and Ni38 Fe20 Cr10 Mn16 Co16, exhibited passivity and localized corrosion. The passivity observed in these low chromium MPEAs is likely derived from their relatively high nickel content. Crystallographic pit morphology was observed in most of these MPEAs, suggesting the absence of a salt film on the dissolving pit surface. Such crystallographic pit morphology indicates that the pit growth in most of these MPEAs was under charge-transfer/ohmic control.